NEED FOR HUMANIZED CARE IN HOSPITALIZED ELDERLY PEOPLE - Eduardo da Silva Ferreira, Carlos; Barros de Quental, Ocilma; Caroline de Souza, Anne; Ruston Oliveira Braga, Thárcio (Health and Society, 2023)
Introduction: Humanization is one of the main tools for achieving active and healthy aging that must be seen in addition to performing health care techniques. In this way, the need for assistance and humanized care arises, thus seeking to prevent, promote, or even rehabilitate the elderly according to their degree of fragility. Objective: To identify the needs of hospitalized elderly, highlighting humanized care; as well as the importance, difficulties and strategies for humanized care for the hospitalized elderly. Methodology: Integrative Review Research, with a qualitative approach to the data, with Evidence-Based Practice (EBP). Conducted through data collection through digital research in databases indexed in the VHL: LILACS, SCIELO, BDenf and MEDLINE. Sample obtained by pre-defined descriptors. Data collection through the crossing of descriptors with inclusion and exclusion criteria; method of exploratory readings, with a critical and analytical approach; with data analysis based on comparison. Final Considerations: It was found that studies on this topic reveal the importance of multidisciplinary health care in the face of humanized care for the hospitalized elderly, having a holistic view and, above all, in the care provided for this demand.